REVITALISASI TRADISI LISAN SEBAGAI UPAYA PELESTARIAN BUDAYA LOKAL DI ERA MODERN - Alya Revalina Achmad; Rosma Natasia; Abdul Haliq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Revitalization of oral traditions in Indonesian Language and Literature learning is an important step in preserving local culture and strengthening national identity. Oral traditions such as folklore, pantun, and poetry contain moral values ​​and local wisdom that can be used as teaching materials to improve students' literacy skills. This article aims to examine the importance of integrating oral traditions into learning and its implementation strategies in the classroom. With a descriptive qualitative approach and literature review, it was found that teachers have a strategic role in guiding students to rewrite and document oral stories. Through this activity, students not only practice language skills but also contribute to cultural preservation. This effort supports the mandate of Law No. 5 of 2017 concerning the Advancement of Culture, while strengthening the character and identity of the nation through education